Exploring Cultural Memory Through Political Economy—Manufacturing History in the Documentary The Battle for Hitler’s Supership (2005) - Bockwoldt, Juliane C (Nordlit, 2019)
This article suggests supplementing Astrid Erll’s framework for analysis of memory making media with key insights from Herman and Chomsky’s propaganda model. An analysis of the documentary The Battle for Hitler’s Supership that portrays the story of the German battleship Tirpitz, which the British Royal Air Force sunk in Tromsø in 1944, will illustrate the benefits of this approach. The combination of a formal analysis with an examination of the structural conditions that predispose the medium’s appearance provide valuable insights into how and why a specific dominant message that is conveyed by the documentary emerges. I show that the political economy behind the TV production has an impact on the documentary’s content and form and argue that the evolving narrative not only depicts a story about the specific events of November 1944 but also about current national self-perceptions and self-presentations.